Deletion of diacylglycerol-responsive TRPC genes attenuates diabetic nephropathy by inhibiting activation of the TGFβ1 signaling pathway - Liu, Benju (2017)
TRPC6 plays a critical role in proteinuric kidney diseases, and TRPC3 is involved in tubulointerstitialdamage and renal fibrosis in obstructed kidneys. Podocyte loss is a characteristic event in diabetic nephropathy(DN). The aim of this study was to examine whether deletion of the closely related diacylglycerol (DAG)-responsiveTRPCs in mice (TRPC3/6/7-/-) affects diabetes-induced renal dysfunction and podocyte loss. We compared urinevolume, kidney hypertrophy, glomerular enlargement, albuminuria and podocyte loss between wild type (WT) andTRPC3/6/7-/- diabetic mice. Finally, we examined whether the TGFβ1 signaling pathway is changed in diabetic WTand TRPC3/6/7-/- mice. TRPC6 protein in the renal cortex was increased in WT diabetic mice. High glucose (HG)treatment increased TRPC6 expression in human podocytes. TRPC3 protein, however, was not altered in eitherdiabetic mice or HG-treated human podocytes. Although diabetic WT and TRPC3/6/7-/- mice had similar levels ofhyperglycemia, the TRPC3/6/7-/- diabetic mice showed less polyuria, kidney hypertrophy, glomerular enlargement,albuminuria, and had lost less podocytes compared with WT diabetic mice. In addition, we observed decreasedexpression of anti-apoptotic Bcl2 and increased expression of pro-apoptotic cleaved caspase 3 in WT diabetic mice,but such changes were not significant in TRPC3/6/7-/- diabetic mice. Western blot and immunohistochemistry revealedthat TGFβ1, p-Smad2/3, and fibronectin were upregulated in WT diabetic mice; however, expression of thesesignaling molecules was not changed in TRPC3/6/7-/- diabetic mice. In conclusion, deletion of DAG-responsiveTRPCs attenuates diabetic renal injury via inhibiting the upregulation of TGFβ1 signaling in diabetic kidneys.